Mecanismos de compensação fisiológica e alocação de recursos no desenvolvimento de Canavalia ensiformis DC. (Leguminosae, Papilionoideae) - Curiel, Aline Cristine (Universidade Federal de São Carlos, 2018)
Vegetative and reproductive phases of plant growth differ in their metabolic activity, which is greater during the reproductive period and consequently, requires more energy. Physiological compensatory mechanisms are alternatives used by plants when the energy demand is greater or resources are scarce, in order to obtain the necessary energy. The main examples are: increase the photosynthetic rates or allocate resources from other organs. This study aimed to verify what physiological compensatory mechanisms Canavalia ensiformis uses to supplement the greater energetic demand during the reproductive phase. The photosynthetic activity was evaluated measuring the parameters: sub-stomatal CO2 concentration, CO2 stomatal conductance, transpiration rate, photosynthetic rate, and leaf temperature. The data collection was done throughout the day using a portable photosynthetic measurement system (LCi-SD). The resource allocation dynamics of the species was evaluated by quantifying the biomass accumulation in plants harvested in the early stages of flowering, fructification and physiological maturity. Canavalia ensiformis flowering was premature and although the leaf number increased, the leaf area decreased between flowering and fructification. The photosynthetic activity parameters were higher during the reproductive phase, except for photosynthetic rate, which was slightly higher during the vegetative phase. The high temperature observed during the data collection suggests that the photosynthetic activity variation is related to climatic conditions and not to the phenological phase. The dry mass values were greater in the fructification stage and the biomass accumulation decreased between this stage and the physiological maturity period, indicating that the energy produced was allocated to the seed production instead to the vegetative growth. There is no evidence of resource allocation from roots, suggesting this species balances resources distribution, not using physiological compensatory mechanisms to obtain the energy required during the reproductive phase.
Physiological compensatory mechanisms and resource allocation in Canavalia ensiformis DC. (Leguminosae, Papilionoideae) growth
Keywords: Crescimento vegetal; Adubação verde; Atividade fotossintética; Plant growth; Green manure; Photosynthetic activity; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL; CIENCIAS BIOLOGICAS::BOTANICA